Evaluating the teratogenicity of the selective ß3-adrenoceptor agonist, CL 316.243 hydrate by employing FETAX (frog embryo teratogenesis assay). (2nd January 2017) - Boga, Ayper; Sertdemir, Yasar; Dogan, Ayse
Abstract: In this study, the frog embryo teratogenesis assay (FETAX – Xenopus ) technique was employed to evaluate the potential teratogenicity of the selective ß-adrenoceptor (AR) agonist, CL 316.243. In this context, CL 316.243 was applied to the South African clawed frog ( Xenopus laevis ) embryos. The media containing the CL 316.24-exposed embryos were monitored and changed/replaced once every 24 hours. Using FETAX, we determined the minimum concentrations to inhibit growth (MCIG) for CL 316.243. The 96-hour no observable adverse effect concentration (NOAEC), the 96-hour lowest observable adverse effect concentration (LOAEC), the 96-hour EC50 (malformation) and the 96-hour LC50 (lethal concentration) for mortality and malformation could not be determined because the used concentrations did not affect viability or the presence of abnormalities. On the other hand, the MCIG of CL 316.243 was determined as 1 mg/L. Our results demonstrated that CL 316.243 administration was associated with no of teratogenic and toxic effects. However, from first concentration we used (1 to 5 mg/L) length of embryos reduced significantly ( p  < 0.001) when compared to control of Xenopus embryos. Further studies should be conducted with different concentrations in order to investigate the optimal concentrations for treating preterm labor with these substances.